A framework for higher academic institutions in the republic of South Africa to mitigate network security threats and attacks. - Mohapi, Matrinta Josephine (Vaal University of Technology, 2017)
The computer networks of higher academic institutions play a significant role in the academic lives of students and staff in terms of offering them an environment for teaching and learning. These institutions have introduced several educational benefits such as the use of digital libraries, cluster computing, and support for distance learning. As a result, the use of networking technologies has improved the ability of students to acquire knowledge, thereby providing a supportive environment for teaching and learning. However, academic networks are constantly being attacked by viruses, worms, and the intent of malicious users to compromise perceived secured systems. Network security threats and cyber-attacks are significant challenges faced by higher academic institutions that may cause a negative impact on systems and Information and Communications Technology (ICT) resources. For example, the infiltration of viruses and worms into academic networks can destroy or corrupt data and by causing excessive network traffic, massive delays may be experienced. This weakens the ability of the institution to function properly, and results in prolonged downtime and the unavailability of Information Technology (IT) services. This research determines challenges faced by higher academic institutions, identifies the type of security measures used at higher academic institutions, and how network security could be addressed and improved to protect against network security threats and attacks. Two research approaches were adopted, namely a survey and an experiment. Survey questionnaires were distributed to IT technical staff at higher academic institutions in Gauteng province to determine the challenges they face in terms of securing their networks. It is crucial that network security takes on a prominent role when managing higher academic institutions‘ networks. The results of the study reveal several challenges such as budget constraints, inadequate security measures, lack of enforcing network security policies, and lack of penetration testing on systems and the network. The results also reveal that the implementation of security measures can and does address network security threats and attacks. It is therefore extremely important for higher academic institutions to implement proper security measures to help mitigate network security threats and attacks. The framework proposed is based on the results from the research study to help mitigate network security threats and attacks at higher academic institutions.
M. Tech. (Department of Information and Communication Technology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Academic networks; Cyber-attacks; Higher academic institutions; Network; Network security attacks; Network security threats; Vulnerabilities; Dissertations, Academic -- South Africa; Computer networks -- Security measures; Computer security; Cyberspace -- Security measures; Computer crimes -- South Africa -- Prevention; Computer crimes -- Prevention